Mamiferos - Theodorou, Rod. (Chicago, Ill. : Heinemann Library, 2007)
Introduces the birth, development, care, feeding, and characteristics of baby mammals.
Includes bibliographical references (p. 32) and index.
Keywords: Spanish language materials; Mammals -- Infancy -- Juvenile literature; Parental behavior in animals -- Juvenile literature